Rotational Atherectomy: A Contemporary Appraisal - Tanush Gupta (Radcliffe Medical Media, 2019)
Rotational atherectomy (RA) is an atheroablative technology that enables percutaneous coronary intervention for complex, calcified coronary lesions. RA works on the principle of ‘differential cutting’ and preferentially ablates hard, inelastic, calcified plaque. The objective of RA use has evolved from plaque debulking to plaque modification to enable balloon angioplasty and optimal stent expansion. The clinical experience over the past 30 years has informed the current best practices for RA with use of smaller burr sizes, short ablation runs a ‘pecking’ motion, and avoidance of sudden decelerations. This has led to significant improvements in procedural safety and a reduced rate of associated complications. This article reviews the principles, clinical indications, contemporary evidence, technical considerations and complications associated with the use of RA.